The Study of Indonesian, Malaysian, and American Consumers' Purchase Decision towards Motorcycle Riding Gear. Case Study : Unionwell. - Markandya, Almira; Aprilianty, Fitri (Journal of Business and Management, 2020)
Abstract. Motorcycle phenomenon has been occurs and increase in several countries including in Indonesia. With the start of motorcycle trends there is also a motorcycle riding gear trend. Motorcycle riding gear is a clothing and accessories that is used by motorcyclist. By the increase in motorcycle riding gear trend there will be an opportunity for motorcycle riding gear business. One of the popular motorcycle riding gear business in Indonesia is Unionwell, a brand that is establish in Indonesia and focus in motorcycle and vintage culture and clothing. Eventually, Unionwell develop new strategy which is expand its store to another countries which are Malaysia and US. There is obstacles that face by Unionwell because each country has different culture and it causes different consumer behaviour. In order to survive and expand in global market, Unionwell must know the consumer behaviour from these 3 countries. This study aims to determine the consumer purchase decision in Indonesia, Malaysia, US and the relationship between the cross-national consumer attitude and purchase decision to help Unionwell with the international marketing recommendation. This study adapted the model from the previous research about cross-cultural and men consumer behaviour. This research use quantitative approach through online survey method towards 200 respondent who already purchase motorcycle riding gear in Unionwell and analyzed by PLS-SEM and One Way MANOVA to assess the relationship between the factors and consumer purchase decision differences among 3 countries (Indonesia, Malaysia, and US). The result shows, attitude towards globalization significantly affected global openness and consumer ethnocentrism. Global openness significantly affected consumer ethnocentrism. Consumer ethnocentrism significantly affected COO image. COO image affectedbrand awareness. Moreover, social identity, self-esteem, culture value and lifestyle affected attitude towards products. Meanwhile, attitude towards product affected purchase decision. The implication of this research is to give insight about consumer attitude and buying behaviour towards motorcycle riding gear and to help Unionwell survive and expand in global market by give the international recommendation that can be implied.Keywords : Attitude, Buying Decision, Cross Culture, Motorcycle Riding Gear, Unionwell